Analysis of Nurses Staff Needs Using Workload Indicate Staff Need in Pediatric Ward With Time Motion Study - Richa Noprianty; Syafitri Anisa Febianti; Jahidul Fikri (Universitas Muhammadiyah Yogyakarta, 2020)
Hospital “X” has implemented the WISN calculation method in determining the need for nurses in the Inpatient Room, but this calculation is applied to all inpatients room with the method work sampling while calculating the need for nurses based on the WISN Method can also use the time and motion study method. The purpose of this study was to determine the analysis of the needs of nurses based on the WISN method. The method was descriptive observational with the One-Shot method. The number of samples was 9 nurses when taking action directly, indirectly and personally both of so obtaining 27 times of observations, with a total 12,960 minutes. Observations were done using time and motion study with 5 steps. The results showed that the morning shift was obtained the results of direct activities were 609.35, indirect activities were 1783.13, and personally were 386.23, while evening shift was obtained the results of direct activities were 1119.26, indirect activities were 1413.46 and personally were 466.18, and the night was obtained the results of direct activities were 700.1, indirect activities were 1541.7, and personally were 2126.22, with total workload standards 422773.6674 hours/years. The final results obtained the need for nurses is 28 people, while which are available is 24 nurses, with the WISN Ratio result, it is found that 0.8 is less than 1. The results of this study can be taken into consideration in reducing the number of nursing staff in the morning shift and added the afternoon shift.